The Influence of Service Quality Dimensions towards Customer Loyalty with Customer Satisfaction as the Mediator for Hokky Supermarket - Christina Christina (iBuss Management, 2020)
This research paper aims to find the relationship between service quality dimensions and customer loyalty with customer satisfaction as the mediator for Hokky supermarket. This research topic was chosen, as service quality dimensions are able to differentiate the businesses under retail industry, knowing the fact that they sell homogenous goods. Moreover, the author also discussed the most dominant service quality dimensions for Hokky supermarket, which shows the dimension that needs to be improved first before the other dimensions. In total, there were 102 respondents’ answers gathered, which was analyzed by using the multiple linear regressions of path analysis, and the sobel test to test the mediation effect. The data was processed using IBM SPSS software. Then, there were four findings, answering the four research questions. The four findings are (1) empathy has the most dominant positive influence toward customer satisfaction, (2) only empathy and responsiveness that have significant and positive influence on customer satisfaction, (3) customer satisfaction has a significant influence on customer loyalty, and (4) the relationship of empathy and responsiveness with customer loyalty has a full mediation effect of customer satisfaction, while the relationship between assurance and customer loyalty has a partial mediation effect of customer satisfaction. Keywords: Service Quality Dimensions, Customer Satisfaction, Customer Loyalty